Planning successful rehearsals - Folks, Steve; Doughty, Ray.; Moody, Bill, 1941-; South Carolina. Office of Instructional Technology; South Carolina Educational Television Network; University of South Carolina. School of Music (Columbia, SC : South Carolina Educational Television Network, 1989)
Presents a lecture by Dr. William J. Moody, Director, School of Music, University of South Carolina, who discusses the essential step in planning rehearsals, the parts of a rehearsal, choice of music, score preparation, morale boosters, and time savers. A brief period of questions and answers follows.
Title on cassette label and container: Sucessful [sic] rehersal [sic].
1263-0015.
Camera operators, Clint Bryson, Don Mills, Robert Rothstein; editor, Elaine Cooper.
Series host: Ray Doughty.
Recorded on Sept. 15, 1989.
Music educators.
Keywords: Music rehearsals